Predictive and prognostic value of aurora kinase A combined with tumor-infiltrating lymphocytes in medullary thyroid carcinoma - Wang, Zhongyu; Guo, Fengli; Fu, Guiming; Zhao, Zewei; Kang, Ning; Hou, Xiukun; Zheng, Xiangqian (Frontiers in Oncology, 2024)
Background: Aurora kinase A (AURKA) and tumor-infiltrating lymphocytes (TILs) are both known to play an essential role in tumorigenesis. However, the expression and prognostic value of the AURKA and TILs in medullary thyroid carcinoma (MTC) have not yet been investigated. Patients and methods : Surgical specimens and clinical data of 137 patients diagnosed with MTC were collected. AURKA expression and TILs infiltration were quantified by immunohistochemistry and hematoxylin-eosin staining. Subsequently, the prognostic value of AURKA expression and TIL infiltration in MTC was evaluated. Results: AURKA was highly expressed in patients with multifocal tumor, cervical lymph node metastasis, and an advanced TNM stage, indicating a high probability of recurrence. AURKA further exhibited a positive correlation with TILs (R = 0.44, P < 0.001). High expression of AURKA combined with a low numbers of TILs (AURKA high /TILs low ) was identified as an independent prognostic factor for biochemical recurrence (odds ratio: 4.57, 95% confidence interval: 1.54-14.66, P < 0.01) and recurrence-free survival (hazard ratio: 3.64, 95% confidence interval: 1.52-8.71, P < 0.001). The combination of AURKA and TILs apparently improves the prognostic value for biochemical recurrence (area under the curve: 0.751) and structural recurrence (area under the curve: 0.836) of MTC. Notably, AURKA high /TILs low demonstrated a high value for prediction of distant or unresectable locoregional recurrence, with an overall accuracy of 86.9%.AURKA high is associated with the MTC malignancy. The combination of AURKA high /TILs low was identified as novel independent prognostic marker in MTC, predicting incurable disease recurrence with high accuracy.